Memahami dan Menjawab Panggilan Tuhan bagi Mahasiswa Teologi: Perspektif Yeremia 1:4-19 - Lela Siska Inriani Samosir; Susilawati Panjaitan; Grecetinovitria M. Butar-Butar (Jurnal Magistra, 2024)
The book of Jeremiah 1:4-19 discusses God's call to the prophet Jeremiah. This research focuses on the response and meaning of the call conveyed in the book of Jeremiah 1:4-19 and its relevance in the lives of today's theology students. This research uses the literature detective method to analyze the meaning of God's call for theology students: the perspective of Jeremiah 1:4-19 so that theology students can understand and respond to that call well. The results show that Jeremiah is a real example of how someone responds to God's call with full dedication and steadfast faith, even though faced with various obstacles and rejection. Jeremiah's calling was not just a duty, but a gift that encouraged him to carry out this duty wholeheartedly. His awareness of this calling was planted from the start, even though it was accompanied by doubts and fears.